Cognitive flexibility, growth mindset, transdisciplinary thinking, and resilience premises for an instructional innovation framework for design-based biology - Honra, Joelash R.; Monterola, Sheryl Lyn C.; Yangco, Rosanelia T.; Muega, Maricris B. Acido; Magbanua, Francis S.; Salubyaba, Teodora M. (Quezon City College of Education, University of the Philippines Diliman, 2024)
Addressing the longstanding concern of bridging theoretical learning with practical applications remains crucial in education. To tackle this challenge, educators must embrace innovative instructional approaches that integrate students’ real-world experiences. This study investigated the synergistic influence of Design-Based Biology Education (DBE) on students’ cognitive flexibility, growth mindset, and transdisciplinary thinking. Moreover, it examined how academic resilience moderates the effects of DBE on these outcome variables, alongside investigating whether transdisciplinary thinking predicts cognitive flexibility and growth mindset among biology students.

The study was conducted using a three-group pretest-posttest quasi-experimental design and involved 141 senior high school students from a public school in Quezon City. These students were divided into three groups: Design-Based Biology Education (DBE), Problem-Based Learning (PBL), and Non-Design-Based Biology Education (NDBE). The researcher employed a parallel lesson plan across all groups, focusing on empathetic understanding as a critical element in the DBE intervention.

Data collection encompassed both quantitative and qualitative methods. Quantitative data were gathered through Likert scales, including the Cognitive Flexibility Inventory (CFI), Mindset Theory Scale (MTS), Filipino Learners’ Academic Resilience Scale (FLARS), and Transdisciplinary Thinking Scale (TTS). The researcher obtained qualitative data from student journal entries, focus group discussions, student output, and daily observational notes. Instrument validation was ensured through expert panels and pilot testing.

Levene’s test assessed the variance in mean pretest ratings across the three intact classes on the four scales, ensuring comparability before intervention. Following this, a one-way analysis of variance (ANOVA) was conducted on the mean posttest ratings of the Likert scales to establish intervention effects. Significant differences were further explored through post-hoc analysis using Tukey’s HSD, with effect size computed to gauge outcome variability attributable to the intervention. Additionally, moderated regression analysis was employed to explore whether academic resilience moderated the impact of DBE on cognitive flexibility, growth mindset, and transdisciplinary thinking. Subsequently, simple linear regression analysis investigated whether transdisciplinary thinking positively predicted both cognitive flexibility and growth mindset. Furthermore, qualitative analyses complemented these findings, with thematic analysis enriching the interpretation of quantitative data. As a result, an emergent instructional innovation framework emerged from the interaction between independent and dependent variables, providing valuable insights into effective instructional strategies.

The results highlighted the significant impact of teaching approaches, particularly the integration of empathetic elements, on student outcomes. Notably, Design-Based Biology Education (DBE) emerged as a potent enhancer of students’ cognitive flexibility, growth mindset, and transdisciplinary thinking. Conversely, Problem-Based Learning (PBL) demonstrated effectiveness primarily in improving students’ transdisciplinary thinking. Moreover, academic resilience played a paramount role in moderating the effects of DBE on the outcome variables, with its influence varying across different levels of resilience. Furthermore, the study explained the positive prediction of transdisciplinary thinking on students’ cognitive flexibility and growth mindset. From these findings, five core teaching strategies surfaced, describing essential elements for effective instructional innovation. These strategies encompassed integrating the design thinking process with empathetic approaches, fostering resilience through tailored activities, promoting interdisciplinary projects and collaborative learning, explicit instruction on growth mindset principles, adopting authentic assessment methods. Together, these strategies formed the foundation of the emergent instructional innovation framework, offering valuable insights for educators seeking to optimize student learning experiences.

Implications of the findings extend to improving biology education by addressing theory-practice gaps through DBE. Moreover, future research avenues could explore the broader impact of Design-Based Biology Education (DBE) on additional constructs such as systems thinking, engagement, critical thinking, and metacognitive self-regulation, all of which emerged as significant themes from the qualitative data. These avenues promise a deeper understanding of how DBE influences various facets of student learning and development. Furthermore, there is scope for conducting parallel studies that address the limitations identified in this research. By refining methodologies, expanding sample sizes, or exploring different educational contexts, subsequent studies can further clarify DBE implementation and its effects on student outcomes. Such parallel investigations would enrich the existing body of literature and contribute to the ongoing discourse surrounding innovative instructional approaches in biology education.
Dissertation
Includes bibliographical references (396-409 leaves)
Keywords: Biology -- Study and teaching (Secondary) -- Philippines -- Quezon City; High school students -- Philippines -- Quezon City -- Attitudes; Computer-assisted instruction; Problem solving; Instructional systems -- Design